3D printing of different fibres towards HA/PCL scaffolding induces macrophage polarization and promotes osteogenic differentiation of BMSCs - Jiaxiang Song; Shuai Huang; Xitao Linghu; Hengpeng Wu; Zhenyu Wen; Xiang Li; Qiping Huang; Weikang Xu; Qingde Wa (PLoS ONE, 2025)
With the rise of bone tissue engineering (BET), 3D-printed HA/PCL scaffolds for bone defect repair have been extensively studied. However, little research has been conducted on the differences in osteogenic induction and regulation of macrophage (MPs) polarisation properties of HA/PCL scaffolds with different fibre orientations. Here, we applied 3D printing technology to prepare three sets of HA/PCL scaffolds with different fibre orientations (0–90, 0-90-135, and 0-90-45) to study the differences in physicochemical properties and to investigate the response effects of MPs and bone marrow mesenchymal stem cells (BMSCs) on scaffolds with different fibre orientations. The results showed that multi-angle staggered fibres affected the overall porosity and compressive strength of the scaffolds. Compared with the other two groups, the 0-90-45 scaffold induced osteogenic differentiation of BMSCs more significantly, while promoting the polarisation of MPs towards the M2 phenotype to form an osteogenic-friendly immune microenvironment. Unexpectedly, the 0-90-45 scaffold significantly upregulated the expression of angiogenic genes (PDGF, VEGF). Therefore, we conclude that the multi-angle interlaced fibres better mimic the physiological structure of cancellous bone, and that the excellent biomimetic properties reflect the best in vitro osteogenic, immunomodulatory and angiogenic effects. In conclusion, this study is a step forward in the exploration of BET scaffolds and provides a very promising bone filling material.